The young felons in Brazil: between the protection and the invisibility in the socio-educational system. - Marinho, Fernanda Campos; Santos, Marcos Antônio Sousa dos; Galinkin, Ana Lúcia (Universidade de Brasília, 2019)
The objective of this study is to analyze the practices of justice towards young felons in Brazil, seeking to reflect, in the light of Brazilian legal culture, the ambiguities and consequences of a "punitive treatment" offered to them. It reflects on the ambiguity expressed in the ideal of recovery of the young people considered "deviants" in Brazil. As a background for understanding the meaning of practices and discourses, transformations and permanencies, one can call the particularities of a Brazilian "legal culture". Therefore, a historical review of previous and subsequent practices to the Statute of the Child and the Adolescent (ECA) is carried out, as well as an analysis of the experiences and meanings built by ex-offenders. The idea of ”‹”‹resocializing someone is a modern invention that, in Brazil, is based on an ambivalent logic between punitive and caring justice. The peculiarities of the Brazilian legal culture provide, in part, elucidations for the development of this process in an unequal and hierarchical society. The rhetoric of universal human rights takes on a very specific meaning in our society: the right of the more human and less human. The invisibility of ex young felons in the country is illustrative of this problem.